Stratification Failure Mechanism of Coal Pillar Floor Strata with Different Strength in Short Distance Coal Seams. (15th July 2022) - He, Fulian; Kang, Qingtao; Yin, Shuaifeng; Liu, Yuli; Wang, Zhishuai; Gao, Linsheng
Abstract : The failure of strata with different strength under coal pillar in close distance coal seams has its particularity. Theoretical analysis, numerical simulation, and similar test were used to obtain the failure mechanism of the soft and hard stratification of floor strata under the boundary of wide coal pillar and make out the influence of the strata failure on roadway layout. It shows that the failure of the soft and hard stratification is not synchronous and with different failure forms. The deformation and plastic failure of the soft strata occurs at first; then the fracture of the main bearing hard stratum occurs. Based on the main bearing stratum unbalanced forces acted by upper and lower strata, the initial fracture position and broken blocks span were calculated by bending fracture mechanics model of ultimate span beam. The coal pillar side of the roadway under coal pillar forms "column-beam-column" superimposed structure. The roadway layout under coal pillar and under coal pillar boundary with close distance has large influence on the plastic extension of the "column-beam-column" superimposed structure and the broken of main bearing stratum. The influence of roadway arrangement in floor strata outside coal pillar is smaller than those under coal pillar. It is difficult to control the deformation of roadway surrounding rock if the roadway locates beneath the broken blocks of the main bearing stratum.